2011
DOI: 10.1007/s11511-011-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

A hereditarily indecomposable $ {\mathcal{L}_{\infty}} $-space that solves the scalar-plus-compact problem

Abstract: We construct a hereditarily indecomposable Banach space with dual space isomorphic to ℓ1. Every bounded linear operator on this space is expressible as λI + K with λ a scalar and K compact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
383
0
10

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(398 citation statements)
references
References 37 publications
4
383
0
10
Order By: Relevance
“…Moreover, σ(0) is not on the curve σ(Γ). Proof of [1]: The map z → 1/(z + 1) takes the unit disk onto the half plane {w : Re (w) > 1/2} ⊂ {w : −π/2 < arg(w) < π/2} with the curve Γ going to the line Re (w) = 1/2, where {e iθ : −π < θ < 0} is mapped to {1/2 + iy : y > 0} and the other half of the circle to the other half of the line. This means z → 1/ √ z + 1 maps the disk into a subset of {w : −π/4 < arg(w) < π/4} and the point x + iy is in the image of the disk under this map if and only if (x + iy) 2 satisfies Re (x + iy) 2 > 1 2 .…”
Section: A New Example Of a Universal Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, σ(0) is not on the curve σ(Γ). Proof of [1]: The map z → 1/(z + 1) takes the unit disk onto the half plane {w : Re (w) > 1/2} ⊂ {w : −π/2 < arg(w) < π/2} with the curve Γ going to the line Re (w) = 1/2, where {e iθ : −π < θ < 0} is mapped to {1/2 + iy : y > 0} and the other half of the circle to the other half of the line. This means z → 1/ √ z + 1 maps the disk into a subset of {w : −π/4 < arg(w) < π/4} and the point x + iy is in the image of the disk under this map if and only if (x + iy) 2 satisfies Re (x + iy) 2 > 1 2 .…”
Section: A New Example Of a Universal Operatormentioning
confidence: 99%
“…More recently, a rather striking affirmative result in the Banach space context has been provided by Argyros and Hydon [1], who constructed an infinite dimensional Banach space such that every linear bounded operator is a compact perturbation of a scalar operator. Therefore, by Lomonosov's Theorem, every linear bounded operator in this Banach space has a nontrivial closed hyperinvariant subspace.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar argument holds if x ∈ σ * (F ) \ F . Thus (1) implies (2). Conversely, when (2) holds, let (a α ) be a weak * -null net in 1 (Z) and let x ∈ F .…”
Section: Shift-invariant Predualsmentioning
confidence: 96%
“…In [8], a predual Y of 1 (Z) was constructed such that Y has the Radon-Nikodym property and each infinite-dimensional subspace of Y contains a further infinite-dimensional subspace which is reflexive. This construction was an inspiration for the recent solution to the scalar-compact problem [2]: this exotic Banach space is also an 1 predual. Indeed, in [15], it is shown that if X is any Banach space with separable dual, then there is an 1 predual E which contains an isomorphic copy of X.…”
Section: Introductionmentioning
confidence: 98%